Synthesis of new D-A1–D-A2 type low bandgap terpolymers based on different thiadiazoloquinoxaline acceptor units for efficient polymer solar cells. Issue 75 (26th July 2016) - Keshtov, M. L.; Kuklin, S. A.; Radychev, N. A.; Ostapov, I. E.; Nikolaev, A. Y.; Konstantinov, I. O.; Krayushkin, M. M.; Koukaras, E. N.; Sharma, Abhishek; Sharma, G. D.
Abstract : Two low bandgap D-A1–D-A2 conjugated (with/without fluorine substitution) copolymers, with benzothiadiazole and thiadiazoloquinoxaline acceptors, were used to fabricate BHJ polymer solar cells that achieved up to 7.21% power conversion efficiency. Abstract : Two low bandgap D-A1–D-A2 conjugated copolymers, namely denoted asP1 (non-fluorine substituted thiadiazoloquinoxaline A2) andP2 (fluorine substituted thiadiazoloquinoxaline A2) with the same D (thiophene) and A1 (benzothiadiazole) groups were synthesized in order to investigate the effect of fluorine atoms on the photovoltaic performance of polymer solar cells. The electrochemical properties demonstrate that the highest occupied molecular orbital (HOMO) energy level lowered from −5.08 eV (forP1 ) to −5.16 eV (forP2 ), whereas the lowest unoccupied molecular orbital (LUMO) energy levels remain nearly the same. These copolymers showed strong absorption in the wavelength range 300–1100 nm and have a bandgap of around 1.08 and 1.11 eV forP1 andP2, respectively. After the optimization of the weight ratio and concentration of solvent additives 1-chloronaphathalene (CN), the highest power conversion efficiencies of bulk heterojunction polymer solar cells achieved were up to 5.30% and 7.21% forP1 andP2 as donor and PC71 BM as acceptor. The enhanced V oc and J sc for theP2 based device can be mainly ascribed to the lower HOMO energy levels and higher hole mobility and better morphology of the fluorinated copolymerP2  : PC71 BM blend.